Timing of respiratory virus molecular testing in emergency departments and its association with patient care outcomes: a retrospective observational study across six Australian hospitals. Issue 8 (8th August 2019) - Wabe, Nasir; Li, Ling; Dahm, Maria R; Lindeman, Robert; Yimsung, Ruth; Clezy, Kate; Thomas, Judith; Varndell, Wayne; Westbrook, Johanna; Georgiou, Andrew
Abstract : Objective: A rapid molecular diagnostic test (RMDT) offers a fast and accurate detection of respiratory viruses, but its impact on the timeliness of care in the emergency department (ED) may depend on the timing of the test. The aim of the study was to determine if the timing of respiratory virus testing using a RMDT in the ED had an association with patient care outcomes. Design: Retrospective observational study. Setting: Linked ED and laboratory data from six EDs in New South Wales, Australia. Participants: Adult patients presenting to EDs during the 2017 influenza season and tested for respiratory viruses using a RMDT. The timing of respiratory virus testing was defined as the time from a patient's ED arrival to time of sample receipt at the hospital laboratory. Outcome measures: ED length of stay (LOS), >4 hour ED LOS and having a pending RMDT result at ED disposition. Results: A total of 2168 patients were included. The median timing of respiratory virus testing was 224 min (IQR, 133–349). Every 30 min increase in the timing of respiratory virus testing was associated with a 24.0 min increase in the median ED LOS (95% CI, 21.8–26.1; p<0.001), a 51% increase in the likelihood of staying >4 hours in ED (OR, 1.51; 95% CI, 1.41 to 1.63; p<0.001) and a 4% increase in the likelihood of having a pending RMDT result at ED disposition (OR, 1.04; 95% CI, 1.02 to 1.05; p<0.001) after adjustment for confounders. Conclusion: The timing of respiratory virus molecular testing in EDs was significantly associated with a range of outcome indicators. Results suggest the potential to maximise the benefits of RMDT by introducing an early diagnostic protocol such as triage-initiated testing.